Pediatric and young adult ovarian masses: clinical approach, diagnostic evaluation, and management - Bayramoglu, Zeynep; Timur, Buket; Kızmazoglu, Deniz; Timur, Hikmet Tunc; Ulusoy, Oktay; Aktas, Safiye; Olgun, Nur; Kurt, Sefa (Frontiers in Pediatrics, 2025)
ObjectiveTo evaluate the clinical, pathological, and surgical characteristics of ovarian masses in pediatric and young adult patients, with emphasis on malignancy risk, surgical approach, recurrence, and fertility outcomes.Materials and methodsThis retrospective cohort study included 1,128 female patients under the age of 30 who underwent surgery for ovarian masses between 2003 and 2024. Clinical presentation, imaging, tumor markers, surgical procedures, histopathology, and recurrence were analyzed.ResultsThe mean age of patients was 13.7 ± 4.02 years. Right-sided masses were more common (69.6%), and 79.9% of surgeries were open. Benign tumors were predominant (most commonly mature cystic teratomas), while dysgerminomas were the most frequent malignant neoplasms. Tumor size was significantly larger in malignant cases (p < 0.005). AFP and β-hCG demonstrated high specificity (88% and 90%, respectively) in predicting malignancy. Fertility-sparing surgery was performed in a large proportion of cases. Recurrence was observed in 31% of borderline tumors, 33% of grade 2–3 immature teratomas, 5% of grade 1 immature teratomas, and 12% of malignant germ cell tumors. Laparoscopic procedures, performed in 20% of patients, were associated with better ovarian preservation. Due to the retrospective design, long-term fertility outcomes were not systematically available.ConclusionOvarian masses in pediatric and young adult patients are mostly benign, but a notable risk of malignancy remains, especially in older adolescents and young adults. Tumor markers and imaging aid in preoperative risk stratification. Fertility-sparing surgery is feasible and should be prioritized. However, recurrence rates vary by histology, highlighting the need for structured long-term follow-up in this population.